HUBUNGAN KOMPETENSI DENGAN STRES KERJA PADA PERAWAT DI INSTALASI RAWAT INAP RS BHAYANGKARA BRIMOB DEPOK - Ganis Eka Madani (2021)
Competency of nurses is one of the important aspects in service. The incompatibility between the competence of nurses and the required standards will lead to the risk of errors at work, which is one of the triggers of work stress. Work stress on nurses also affects the quality of hospital services. This study aims to determine the relationship between competence and work stress on nurses at the Inpatient Installation of Bhayangkara Brimob Hospital Depok. The research design is quantitative with a cross sectional approach. The sampling technique used is total sampling with 27 respondents. Data analysis applied was Chi-Square test at 95% CI. The results of statistical tests showed that there was no significant relationship between age (p-value = 1,000), gender (p-value = 1,000), marital status (p-value = 0.424), education level (p-value = 1,000), and tenure (p-value = 0.706) with work stress on nurses. In addition, the results also showed that there was a significant relationship between competence and work stress on nurses at the Inpatient Installation of Bhayangkara Brimob Hospital Depok (p-value = 0.001). The directors and hospital management are expected to improve the basic competence of nurses in inpatient rooms in providing nursing care through seminars and training that are held regularly and continuously in order to minimize work stress.